Analisis Putusan Terhadap Tindak Pidana Bagi Anak Sebagai Pelaku Kejahatan Pencurian Dengan Kekerasan (Studi Putusan No. 77/Pid.Sus-Anak/2023/PN Mdn) - Chairany, Dian Nitha; Zulyadi, Rizkan; Nasution, Alvin Hamzah (JUNCTO: Jurnal Ilmiah Hukum, 2024)
Violent theft is an unavoidable problem in every society. And theft with violence is one of the most common crimes. The crime of theft with violence is stealing something that does not belong to him accompanied by an act against the physical by using considerable force or body strength and aimed at the person who is the object of theft and causing the person to become helpless. The problem in this study is How is the regulation of criminal law for children as perpetrators of violent theft crimes and How is the judge's consideration of criminal offenses for children as perpetrators of violent theft crimes in decision No. 77/Pid.Sus-Child/2023/PN Mdn). The research method is normative juridical. The data obtained is sourced from secondary data. Theft is an act with the aim of taking other people's property illegally without the owner's permission. According to Mahmud Mulyadi, theft with violence is the same as robbery.